Cash Waqf in Indonesia: Wordcloud and Research Cluster - Uula, Mimma Maripatul; Izza, Nadia Nurul; Ikhwan, Ihsanul (SMART Insight, 2023)
This study seeks to map research related to cash waqf in Indonesia published by Dimensions indexed journals from 2008 to 2023. NVivo 12 Plus was used to conduct a thematic review and frequency was used to evaluate 208 publications in the scientific literature. The results found that the number of publications fluctuated from year to year related to cash waqf research in Indonesia, indicating that this topic is an interesting topic and should continue to be developed. In addition, various focuses of discussion and cluster analysis that describe the research path in cash waqf research in Indonesia include Cash Waqf Institution in Indonesia, Cash Waqf in Indonesia and Cash Waqf Model in Indonesia. This research can be used as a starting point for experts to build graphic visualizations of cash waqf research patterns in Indonesia in published scientific research.